Magnetic powder

JP2026170605APending Publication Date: 2026-10-22SANYO SPECIAL STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025064236
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0010】 この粉末を含む磁性部材は、高周波域にある電磁波ノイズを十分に吸収する。この磁性部材は、電子機器の誤動作を抑制しうる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170605000001_ABST
    Figure 2026170605000001_ABST
Patent Text Reader

Abstract

To provide a magnetic sheet 2 that can sufficiently absorb electromagnetic waves in a high frequency range. 【Solution Means】A magnetic sheet 2 has a matrix 4 and a powder dispersed in this matrix 4. The powder is an aggregate of a large number of flat particles 6. The material of these flat particles is an Fe-based alloy. This alloy contains C: 3.0 mass% or more and 4.0 mass% or less Cr: 30.0 mass% or more and 45.0 mass% or less N: 0.03 mass% or more and 0.30 mass% or less Si: 0 mass% or more and 1.0 mass% or less Mn: 0 mass% or more and 1.0 mass% or less Mo: 0 mass% or more and 1.0 mass% or less and V: 0 mass% or more and 8.0 mass% or less . The balance consists of Fe and unavoidable impurities. In this powder, the average particle diameter D50 is 200 μm or less, the average thickness Tav is 5.0 μm or less, and the average aspect ratio AR is 5 or more.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present specification relates to a magnetic powder with flat particle shape.

BACKGROUND ART

[0002] Electronic devices such as personal computers and mobile phones have circuits. Due to radio wave noise radiated from electronic components mounted on these circuits, radio wave interference occurs between electronic components and between electronic circuits. Radio wave interference causes malfunctions of electronic devices. For the purpose of suppressing malfunctions, magnetic sheets (electromagnetic wave absorbing sheets) are inserted into electronic devices. Common magnetic sheets contain magnetic powder.

[0003] Japanese Unexamined Patent Application Publication No. 2007-266031 discloses a magnetic core member suitable for non-contact IC tags using RFID (Radio Frequency Identification) technology. Japanese Unexamined Patent Application Publication No. 2011-22661 discloses an electromagnetic induction digitizer with excellent position detection performance. Japanese Unexamined Patent Application Publication No. 2016-39222 discloses an inductor including a magnetic core and a coil. As these magnetic members, sheets in which soft magnetic powder is dispersed in a rubber or resin matrix are known. As materials for soft magnetic powder, Fe-Si-Al alloys and Fe-Si-Cr alloys are known.

PRIOR ART DOCUMENTS

PATENT DOCUMENTS

[0004]

PATENT DOCUMENT 1

PATENT DOCUMENT 2

PATENT DOCUMENT 3

SUMMARY OF THE INVENTION

PROBLEMS TO BE SOLVED BY THE INVENTION

[0005] One of the required properties for magnetic sheets is the ratio of real permeability (μ') to virtual permeability (μ") (μ'' / μ'). Virtual permeability (μ'') is almost undetectable in the low-frequency range. Virtual permeability (μ'') increases sharply when it reaches a certain frequency. Magnetic sheets with a high frequency at which virtual permeability (μ'') shifts sharply are suitable for use in the high-frequency range. For example, magnetic sheets with a frequency FR of over 500 MHz at which tanδ(μ'' / μ') is 0.1 are suitable for use in the high-frequency range. Conventional magnetic sheets using Fe-Si-Al alloy powder generally have a frequency FR of 20 MHz or less. Conventional magnetic sheets using Fe-Si-Cr alloy powder generally have a frequency FR of 50 MHz or less. In recent years, electronic devices have been designed to achieve higher communication speeds. High-frequency radio waves are used for high-speed communication. Suppressing malfunctions caused by electromagnetic noise in the high-frequency range is important. The tanδ(μ'' / μ') of conventional magnetic sheets is insufficient.

[0006] The applicant's intention is to provide a magnetic material that can sufficiently absorb electromagnetic waves in the high-frequency range. [Means for solving the problem]

[0007] The magnetic powder disclosed herein has a large number of flattened particles. The material of these particles is C: 3.0% by mass or more and 4.0% by mass or less Cr: 30.0 mass% or more and 45.0 mass% or less N: 0.03 mass% or more and 0.30 mass% or less Si: 0 mass% or more and 1.0 mass% or less Mn: 0 mass% or more and 1.0 mass% or less Mo: 0 mass% or more and 1.0 mass% or less and V: 0 mass% or more and 8.0 mass% or less This is an alloy containing [a specific component], with the remainder being Fe and unavoidable impurities. The average particle size D50 of this magnetic powder is 200 μm or less. The average thickness Tav of this magnetic powder is 5.0 μm or less. The average aspect ratio AR of this magnetic powder is 5 or greater.

[0008] The material of this magnetic powder may be an alloy that is substantially free of Si, Mn, Mo, and V. The material of this magnetic powder may also be an alloy that contains one or more elements selected from the group consisting of Si, Mn, Mo, and V.

[0009] The magnetic sheet disclosed herein comprises a matrix and magnetic powder dispersed in the matrix. This magnetic powder has a large number of flattened particles. The material of these particles is: C: 3.0% by mass or more and 4.0% by mass or less Cr: 30.0 mass% or more and 45.0 mass% or less N: 0.03 mass% or more and 0.30 mass% or less Si: 0 mass% or more and 1.0 mass% or less Mn: 0 mass% or more and 1.0 mass% or less Mo: 0 mass% or more and 1.0 mass% or less and V: 0 mass% or more and 8.0 mass% or less This is an alloy containing [a specific component], with the remainder being Fe and unavoidable impurities. The average particle size D50 of this magnetic powder is 200 μm or less. The average thickness of this magnetic powder is 5.0 μm or less. The average aspect ratio AR of this magnetic powder is 5 or greater. [Effects of the Invention]

[0010] Magnetic materials containing this powder effectively absorb electromagnetic noise in the high-frequency range. This magnetic material can suppress malfunctions in electronic devices. [Brief explanation of the drawing]

[0011] [Figure 1] Figure 1 is a schematic cross-sectional view showing a portion of a magnetic sheet according to one embodiment. [Figure 2] Figure 2 is an enlarged view showing the flattened particles contained in the magnetic material shown in Figure 1. [Modes for carrying out the invention]

[0012] Hereinafter, preferred embodiments will be described in detail with appropriate reference to the accompanying drawings.

[0013] [Magnetic Sheet] FIG. 1 shows a magnetic sheet 2 (magnetic member). This magnetic sheet 2 has a matrix 4 and magnetic powder dispersed in the matrix 4. A preferred base material for the matrix 4 is a polymer. Typical polymers include rubber and resin. This powder is an aggregate of a large number of particles 6. These particles 6 are capable of absorbing electromagnetic wave noise.

[0014] In the production of this magnetic sheet 2, the powder is kneaded with the base polymer together with various chemicals to obtain a polymer composition. A known method can be adopted for kneading. For example, kneading can be performed using an internal kneader, open rolls, or the like. Examples of the chemicals include processing aids such as lubricants and binders. The polymer composition may further contain a flame retardant.

[0015] Next, the magnetic sheet 2 is formed from this polymer composition. A known method can be adopted for forming. The forming can be performed by a compression molding method, injection molding method, extrusion molding method, rolling method, or the like.

[0016] The shape of the magnetic member is not limited to a sheet shape. The magnetic member may have shapes such as a ring shape, cubic shape, rectangular parallelepiped shape, and cylindrical shape. This powder is also suitable for magnetic members having more complex shapes.

[0017] In the magnetic sheet 2 (magnetic member), the frequency FR at which tanδ (μ'' / μ'), represented by the ratio of the real part permeability μ' to the imaginary part permeability μ'', reaches 0.1 is preferably 500 MHz or higher. The magnetic sheet 2 having a frequency FR of 500 MHz or higher sufficiently absorbs electromagnetic wave noise in the high frequency range. From this viewpoint, the frequency FR is preferably 600 MHz or higher, and particularly preferably 650 MHz or higher.

[0018] [Particle Shape] Figure 2 shows a cross-section of a single particle 6. In Figure 1, the symbol L1 indicates the length of the major axis of particle 6, and the symbol T1 indicates the thickness of particle 6. Length L1 is greater than thickness T1. In other words, the shape of this particle 6 is flattened.

[0019] The flattened particles 6 exhibit shape anisotropy. This anisotropy can contribute to the high real permeability μ' of the magnetic sheet 2. Moreover, in a magnetic sheet 2 containing flattened particles 6 with a small thickness T1, eddy current losses are suppressed, making relaxation of the real permeability μ' less likely. In this magnetic sheet 2, the frequency FR at which tanδ(μ'' / μ'), expressed as the ratio of the real permeability μ' to the imaginary permeability μ'', reaches 0.1 is high. This magnetic sheet 2 can absorb electromagnetic noise in the high-frequency range.

[0020] The average Tav of the thickness T1 is preferably 5.0 μm or less. Eddy current loss is suppressed in magnetic sheet 2 containing powder with an average thickness Tav of 5.0 μm or less. The frequency FR at which tanδ(μ'' / μ') reaches 0.1 in this magnetic sheet 2 is high. From this viewpoint, an average thickness Tav of 3.0 μm or less is more preferable, and 2.0 μm or less is particularly preferable. From the viewpoint of ease of powder manufacturing, an average thickness Tav of 0.1 μm or more is preferred, 0.5 μm or more is more preferable, and 1.0 μm or more is particularly preferable.

[0021] The average aspect ratio AR of this powder is preferably 5 or higher. In a magnetic sheet 2 containing powder with an average aspect ratio AR of 5 or higher, the real permeability μ' and imaginary permeability μ'' in the high-frequency range are sufficiently large. From this viewpoint, an average aspect ratio AR of 15 or higher is more preferable, and 20 or higher is particularly preferable. An average aspect ratio AR of 100 or lower is preferred. In a magnetic sheet 2 containing powder with an average aspect ratio AR of 100 or lower, the areas where particles 6 come into contact with each other are suppressed, and losses due to eddy currents are suppressed. From this viewpoint, an average aspect ratio AR of 70 or lower is more preferable, and 50 or lower is particularly preferable.

[0022] For measuring the length L1, thickness T1, and aspect ratio, a resin-embedded sample is used that allows observation of the thickness direction of the flattened particle 6. This sample is polished, and the polished surface is observed using a scanning electron microscope (SEM). The magnification of the image during observation is 500x. In the analysis of this image, the image data is binarized. When the binarized image of particle 6 is approximated as an ellipse, the length of the major axis is the length L1, the length of the minor axis is the thickness T1, and the ratio of the two (length of the major axis / length of the minor axis) is the aspect ratio of each particle 6. These results are given an arithmetic mean to calculate the average thickness Tav and average aspect ratio AR of the powder.

[0023] [Particle material] The material of the flattened particle 6 is an Fe-based alloy. This Fe-based alloy is C: 3.0% by mass or more and 4.0% by mass or less Cr: 30.0 mass% or more and 45.0 mass% or less and N: 0.03 mass% or more and 0.30 mass% or less It contains [a specific compound]. Preferably, the remainder of this alloy is Fe and unavoidable impurities.

[0024] This Fe-based alloy may contain one or more elements selected from the group consisting of Si, Mn, Mo, and V. Preferably, the Si content is 0% to 1.0% by mass, the Mn content is 0% to 1.0% by mass, the Mo content is 0% to 1.0% by mass, and the V content is 0% to 8.0% by mass. That is, this Fe-based alloy is C: 3.0% by mass or more and 4.0% by mass or less Cr: 30.0 mass% or more and 45.0 mass% or less N: 0.03 mass% or more and 0.30 mass% or less Si: 0 mass% or more and 1.0 mass% or less Mn: 0 mass% or more and 1.0 mass% or less Mo: 0 mass% or more and 1.0 mass% or less and V: 0 mass% or more and 8.0 mass% or less It contains [a specific compound]. Preferably, the remainder of this alloy is Fe and unavoidable impurities.

[0025] [Method for producing powder] In the production of powder, first, the raw material powder is prepared. The raw material powder can be obtained by atomization, grinding, etc. Atomization is particularly preferred. In atomization, the molten metal is rapidly cooled. This rapid cooling can yield particles 6 that contain a large amount of martensite. Examples of atomization methods include gas atomization, water atomization, and disc atomization. Gas atomization and disc atomization are preferred. In gas atomization, the raw material metal is heated and melted to obtain molten metal. This molten metal flows out of a nozzle. Gas (argon gas, nitrogen gas, etc.) is blown onto this molten metal. Due to the energy of this gas, the molten metal is pulverized into droplets, which are cooled as they fall. These droplets solidify, forming particles 6. In disc atomization, the raw material metal is heated and melted to obtain molten metal. This molten metal flows out of a nozzle. This molten metal is dropped onto a rapidly rotating disc. The molten metal is rapidly cooled and solidified to obtain particles 6.

[0026] The raw material powder is subjected to classification and primary heat treatment as needed. The hardness of the raw material powder can be adjusted by the primary heat treatment. From the raw material powder that has undergone primary heat treatment, a powder with a large average aspect ratio AR can be obtained by flattening, which will be described in detail later. The temperature of the primary heat treatment is preferably between 300°C and 1200°C. Primary heat treatment at 300°C or higher softens the raw material powder sufficiently. From this viewpoint, a temperature of 500°C or higher is particularly preferred. Primary heat treatment at 1200°C or lower suppresses sintering of the raw material powder. From this viewpoint, a temperature of 1100°C or lower is more preferable, and 900°C or lower is particularly preferred.

[0027] This raw material powder is subjected to a flattening process. Typical flattening is performed using an attritor. The flattening process yields flattened particles 6.

[0028] This powder is subjected to a secondary heat treatment. The secondary heat treatment reduces the retained austenite phase in the powder and increases the saturation magnetization. Furthermore, the secondary heat treatment causes a transformation equivalent to age hardening. In the magnetic sheet 2 containing powder having the structure obtained by this transformation, the frequency FR at which tanδ(μ” / μ') reaches 0.1 is large. The temperature of the secondary heat treatment is preferably 300°C or higher, and particularly preferably 500°C or higher. The temperature of the secondary heat treatment is preferably 900°C or lower, more preferably 850°C or lower, and particularly preferably 800°C or lower.

[0029] [Saturation magnetization Ms] The saturation magnetization Ms of the magnetic powder is preferably 0.60T or higher. The frequency FR at which tanδ(μ” / μ') of the magnetic sheet 2 containing this powder reaches 0.1 is high. This magnetic sheet 2 can absorb electromagnetic noise in the high-frequency range. From this viewpoint, a saturation magnetization Ms of 0.65T or higher is particularly preferred. The saturation magnetization Ms is measured using a vibrating sample magnetometer (VSM). The measurement conditions are as follows. Maximum applied magnetic field: 1204kA / m Powder mass: approximately 70 mg

[0030] [Average particle size D50] From the viewpoint of obtaining a magnetic sheet 2 with a smooth surface, the average particle size D50 of the powder is preferably 200 μm or less, more preferably 100 μm or less, and particularly preferably 70 μm or less. From the viewpoint of achieving a large average aspect ratio AR, the average particle size D50 is preferably 10 μm or more. The average particle size D50 is the particle diameter at the point where the cumulative curve reaches 50% when the cumulative curve is determined with the total volume of the powder as 100%. The average particle size D50 is measured, for example, by Nikkiso's laser diffraction / scattering particle size distribution analyzer "Microtrac MT3000". The powder is poured into the cell of this device together with pure water, and the average particle size D50 is detected based on the light scattering information of the particles 6.

[0031] [Tap Density TD] From the viewpoint of obtaining a homogeneous magnetic sheet 2 with a smooth surface, the tap density TD of the powder is 2.5 g / cm³.3 The following is preferable: 2.3 g / cm³ 3 The following is more preferable: 2.2 g / cm³ 3 The following is particularly preferable: Tap density TD is 0.3 g / cm³. 3 The above is preferable. The tap density TD is measured in accordance with the provisions of "JIS Z 2512". In the measurement, approximately 40g of powder is used in a volume of 100cm³. 3 It is filled into the cylinder. The measurement conditions are as follows: Drop height: 50mm Number of taps: 200

[0032] [element] The roles of each element are explained in detail below.

[0033] [C (carbon)] The Fe-based alloy of particle 6 contains an appropriate amount of carbon. During the grinding or flattening process to obtain these particles 6, martensite containing a large amount of carbon and dislocations is induced. In the magnetic sheet 2 containing these particles 6, the frequency FR at which tanδ(μ” / μ') reaches 0.1 is large. Furthermore, in the carbon-containing particles 6, an appropriate amount of carbides are generated by secondary heat treatment. From these viewpoints, the carbon content in the Fe-based alloy is preferably 3.0 mass% or more, more preferably 3.2 mass% or more, and particularly preferably 3.4 mass% or more. From the viewpoint of achieving a sufficiently large powder saturation magnetization Ms, the carbon content is preferably 4.0 mass% or less, more preferably 3.8 mass% or less, and particularly preferably 3.6 mass% or less.

[0034] [Cr (chromium)] Cr combines with C to form carbides. These carbides are a resistance factor for magnetic domain wall movement. Powders containing these carbides have high coercivity. In magnetic sheet 2 containing powder with high coercivity, the frequency at which the imaginary permeability (μ") increases sharply can be shifted to the high-frequency side. In this magnetic sheet 2, the frequency FR at which tanδ(μ'' / μ') is 0.1 is large. This magnetic sheet 2 is suitable for use in the high-frequency band.

[0035] The martensitic transformation initiation temperature of Fe-based alloys containing Cr is low. Cr causes retained austenite to form in the microstructure after primary heat treatment. Particles 6 having this microstructure exhibit excellent ductility despite their high carbon content. These particles 6 are easily flattened. Cr can contribute to the high average aspect ratio AR of the powder.

[0036] Cr can contribute to the corrosion resistance of powders. Furthermore, Cr promotes the solid solution of N into Fe.

[0037] These effects related to Cr are insufficient in powders to which carbide-forming elements other than Cr or N are added alone. Cr is an essential element in this powder. The Cr content in Fe-based alloys is preferably 30.0 mass% or more, more preferably 32.0 mass% or more, and particularly preferably 34.0 mass% or more. From the viewpoint of achieving a sufficiently large powder saturation magnetization Ms, the Cr content is preferably 45.0 mass% or less, more preferably 43.0 mass% or less, and particularly preferably 41.0 mass% or less.

[0038] [N (Nitrogen)] Similar to Cr, N causes retained austenite to form in the microstructure after primary heat treatment. Particles 6 having this microstructure exhibit excellent ductility despite their high C content. Flattening of these particles 6 is easy. N can contribute to the high average aspect ratio AR of the powder. N is less likely to reduce the saturation magnetization Ms of the powder compared to Cr. Furthermore, N can contribute to the high frequency FR of the magnetic sheet 2. From these viewpoints, the N content in Fe-based alloys is preferably 0.03 mass% or more, more preferably 0.04 mass% or more, and particularly preferably 0.05 mass% or more. From the viewpoint of saturation magnetization Ms, the N content is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and particularly preferably 0.15 mass% or less. The N content in the magnetic powder can be adjusted by adjusting the N content in the raw material metal. The N content in the magnetic powder can also be adjusted by atomization with nitrogen gas.

[0039] [Si (Silicon)] Si can contribute to lowering the martensitic transformation initiation temperature of Fe-based alloys. Si can also contribute to lowering the hardness of this alloy. Powders with a large average aspect ratio AR can be obtained from raw material powders containing Si. From these viewpoints, the Si content in Fe-based alloys is preferably 0.1 mass% or more, and particularly preferably 0.2 mass% or more. From the viewpoint of achieving a sufficiently large powder saturation magnetization Ms, the Si content is preferably 1.0 mass% or less, more preferably 0.7 mass% or less, and particularly preferably 0.5 mass% or less. In this Fe-based alloy, Si is not an essential element. Therefore, the material of particle 6 may be an Fe-based alloy that is substantially Si-free. Furthermore, the Si content in the Fe-based alloy may be 0 mass%. An Fe-based alloy with a Si content of 0 mass% may contain Si below the detection limit.

[0040] [Mn (Manganese)] Mn can contribute to lowering the martensitic transformation initiation temperature of Fe-based alloys. Mn can also contribute to lowering the hardness of this alloy. Powders with a large average aspect ratio AR can be obtained from raw material powders containing Mn. From these viewpoints, the Mn content in Fe-based alloys is preferably 0.1 mass% or more, and particularly preferably 0.2 mass% or more. From the viewpoint of achieving a sufficiently large powder saturation magnetization Ms, the Mn content is preferably 1.0 mass% or less, more preferably 0.7 mass% or less, and particularly preferably 0.5 mass% or less. In this Fe-based alloy, Mn is not an essential element. Therefore, the material of particle 6 may be an Fe-based alloy that substantially does not contain Mn. Furthermore, the Mn content in the Fe-based alloy may be 0 mass%. An Fe-based alloy with a Mn content of 0 mass% may contain Mn below the detection limit.

[0041] [Mo (Molybdenum)] Mo can contribute to a decrease in the hardness of the raw material powder alloy. Furthermore, Mo can contribute to a high frequency FR of the magnetic sheet 2. From these viewpoints, the Mo content in the Fe-based alloy is preferably 0.1 mass% or more, and particularly preferably 0.3 mass% or more. From the viewpoint of achieving a sufficiently large powder saturation magnetization Ms, the Mo content is preferably 1.0 mass% or less, more preferably 0.7 mass% or less, and particularly preferably 0.5 mass% or less. In this Fe-based alloy, Mo is not an essential element. Therefore, the material of the particles 6 may be an Fe-based alloy that is substantially free of Mo. Furthermore, the Mo content in the Fe-based alloy may be 0 mass%. An Fe-based alloy with a Mo content of 0 mass% may contain Mo below the detection limit.

[0042] [V (Vanadium)] V can contribute to a decrease in the hardness of the raw material powder alloy. Furthermore, V can contribute to a high frequency FR of the magnetic sheet 2. From these viewpoints, the V content in the Fe-based alloy is preferably 1.0 mass% or more, and particularly preferably 4.0 mass% or more. From the viewpoint of achieving a sufficiently large powder saturation magnetization Ms, the V content is preferably 8.0 mass% or less, more preferably 7.0 mass% or less, and particularly preferably 6.0 mass% or less. In this Fe-based alloy, V is not an essential element. Therefore, the material of the particles 6 may be an Fe-based alloy that substantially does not contain V. Furthermore, the V content in the Fe-based alloy may be 0 mass%. An Fe-based alloy with a V content of 0 mass% may contain V below the detection limit.

[0043] [Fe (iron)] Fe is the main component of this alloy. Fe can contribute to the magnetic properties of the powder. From this viewpoint, the Fe content is preferably 30% by mass or more, more preferably 40% by mass or more, and particularly preferably 45% by mass or more. From the viewpoint that the alloy can sufficiently contain C, Cr, and N, the Fe content is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and particularly preferably 60% by mass or less. [Examples]

[0044] The effects of the magnetic powders described in the following examples will be clarified, but the scope disclosed herein should not be interpreted as limiting based on the description of these examples.

[0045] [Example 2] Molten metal was poured through the nozzle of a crucible made of alumina. Gas was blown onto this molten metal to obtain raw material powder. This raw material powder was subjected to classification. This raw material powder was subjected to primary heat treatment at 500°C. This raw material powder was flattened using a wet attritor. For this flattening, a ball made of SUJ2 with a diameter of 4.8 mm was used. In this flattening, ethanol was added to the stirring vessel along with the raw material powder. The rotation speed of this stirring vessel was 300 rpm. Furthermore, this powder was subjected to secondary heat treatment at 500°C to produce the magnetic powder of Example 2 having the composition shown in Table 1 below. The average particle size D50, average thickness Tav, and average aspect ratio AR of this powder are shown in Table 1 below.

[0046] [Examples 1 and 3-13 and Comparative Examples 1-13] Powder was prepared in the same manner as in Example 2, except that the composition of the raw metal, the heat treatment conditions, and the flattening time were changed.

[0047] [Measurement of powder properties] The tap density TD and saturation magnetization Ms of the powder were measured using the method described above. The results are shown in Table 3 below.

[0048] [Measurement of magnetic permeability] A resin composition was obtained by mixing 20 parts by mass of powder with 100 parts by mass of a base resin. A sheet was molded from this resin composition. From this sheet, strip-shaped test pieces with a width of 4 mm and a length of 35 mm were cut out. Using these test pieces, the magnetic permeability at room temperature from 1 MHz to 9 GHz was measured with a PMM-9G1 (manufactured by Ryowa Electronics). Furthermore, the frequency FR at which tanδ(μ” / μ') reached 0.1 was calculated. The results are shown in Table 3 below.

[0049] [Table 1]

[0050] [Table 2]

[0051] In each of the compositions shown in Tables 1 and 2 above, the elemental remainder consists of Fe and unavoidable impurities.

[0052] [Table 3]

[0053] As shown in Table 3, magnetic sheets with a high frequency FR can be obtained from the powders of each example. The superiority of this magnetic powder is clear from these evaluation results. [Industrial applicability]

[0054] The powders described above are suitable for various magnetic materials. [Explanation of Symbols]

[0055] 2. Magnetic sheet 4. The Matrix 6...particles

Claims

1. It has many flattened particles, The material of these particles is C: 3.0% by mass or more and 4.0% by mass or less Cr: 30.0 mass% or more and 45.0 mass% or less N: 0.03% by mass or more and 0.30% by mass or less Si: 0% by mass or more and 1.0% by mass or less Mn: 0 mass% or more and 1.0 mass% or less Mo: 0% by mass or more and 1.0% by mass or less and V: 0% by mass or more and 8.0% by mass or less An alloy containing , with the remainder being Fe and unavoidable impurities, The average particle size D50 is 200 μm or less. The average thickness Tav is 5.0 μm or less. Magnetic powder having an average aspect ratio (AR) of 5 or higher.

2. The magnetic powder according to claim 1, wherein the alloy substantially does not contain Si, Mn, Mo, and V.

3. The magnetic powder according to claim 1, wherein the alloy contains one or more elements selected from the group consisting of Si, Mn, Mo, and V.

4. It comprises a matrix and magnetic powder dispersed in this matrix, The above magnetic powder has a large number of flattened particles, The material of these particles is C: 3.0% by mass or more and 4.0% by mass or less Cr: 30.0 mass% or more and 45.0 mass% or less N: 0.03% by mass or more and 0.30% by mass or less Si: 0 mass% or more and 1.0 mass% or less Mn: 0 mass% or more and 1.0 mass% or less Mo: 0% by mass or more and 1.0% by mass or less and V: 0% by mass or more and 8.0% by mass or less An alloy containing , with the remainder being Fe and unavoidable impurities, The average particle size D50 of the above magnetic powder is 200 μm or less. The average thickness of the above magnetic powder is 5.0 μm or less. A magnetic sheet having an average aspect ratio AR of 5 or more for the magnetic powder described above.

Citation Information

Patent Citations

  • Flat soft magnetic metallic powder and magnetic core member for RFID antenna

    JP2007266031A

  • Position detection apparatus and sensor unit

    JP2011022661A

  • Inductor and method for manufacturing the same

    JP2016039222A